Effect of Open Suctioning of Artificial Airway Based on the Comprehensive Criteria for Suctioning on the Patients\' Hemodynamic Status Hospitalized in the Intensive Care Units - farshid Alazmani Noodeh; farhad ramezanibadr; parvin Shiri Ghidari; taraneh Naghibi mahmoud abadi (Zanjan University of Medical Sciences and Health Services, 2016)
Background and Objectives: Artificial airway suctioning is an important intervention to take care of mechanically ventilated patients. The aim of this research was to determine the effect of artificial airway suction based on the comprehensive criteria for suctioning on the patientschr('39') hemodynamic status in ICU. Materials and Methods: This study was a randomized clinical trial by before-after design with one control group. 60 mechanically ventilated patients admitted to the ICU were selected by convenience sampling and were assigned into two 30-member groups using a block random allocation method. To collect the data, we used demographic and hemodynamic status sheet. In experimental and control groups the need for suctioning was determined on the basis of comprehensive and common suction standards respectively. Hemodynamic status was determined before suctioning and 2 and 5 minutes after suctioning. The data were analyzed by SPSS 17 software. Results: Compare the mean of arterial pressure (MAP) and O2 saturation between two groups respectively showed a significant difference in 2 minutes (P=0.001 and P=0.015) and 5 minutes (P=0.006 and P=0.001) after intervention. The mean difference of MAP (p=0.041), oxygen saturation (p=0.001) and diastolic blood pressure (p=0.021) were significantly different from the Baseline after 2 and 5 minutes of the intervention. Conclusion: It seems suctioning based on comprehensive criteria is effective in preventing side effects and maintaining hemodynamic stability in mechanically ventilated patients.